2019
DOI: 10.1111/joss.12490
|View full text |Cite
|
Sign up to set email alerts
|

Sensory product characterization by consumers using check‐all‐that‐apply questions: Investigations linked to term development using kiwifruit as a case study

Abstract: Sensory product characterization is a cornerstone activity in sensory science, and increasingly it is performed by consumers. Check‐all‐that‐apply (CATA) questions are popular for this purpose, and solid guidelines for many aspects of their implementation exist. However, they do not extend to term development. The present research is situated in this gap, and across 11 consumer studies (n = 1,455) the influence of term variations (e.g., “acid” or “acidic”) and CATA list composition was explored. The descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…According to consumer responses to CATA questions are less discriminative than descriptive analysis DA with trained assessors when dealing with specific flavor characteristics (e.g., "floral"), complex texture attributes (e.g., "smooth"), or attributes with non-consensual meaning for consumers (e.g., "typical Sauvignon blanc"). As previously reported by Jaeger et al (2019), researchers are advised to include consumer-friendly terms in CATA questions and refrain from using technical or not well-understood terms.…”
Section: Discussionmentioning
confidence: 99%
“…According to consumer responses to CATA questions are less discriminative than descriptive analysis DA with trained assessors when dealing with specific flavor characteristics (e.g., "floral"), complex texture attributes (e.g., "smooth"), or attributes with non-consensual meaning for consumers (e.g., "typical Sauvignon blanc"). As previously reported by Jaeger et al (2019), researchers are advised to include consumer-friendly terms in CATA questions and refrain from using technical or not well-understood terms.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main difficulties in applying this test is the actual development of the CATA terms. The CATA terms can have different meanings: they can have a hedonic connotation, or be related to usage occasions or emotions [34,35]. The terms used in this CATA test were selected following both an analysis of the literature on biscuits, quinoa, and GF products [36][37][38][39], and by performing preliminary tests in the laboratory.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The test can be performed by untrained people and it is not demanding for consumers, with a minimum recommendation of N = 60 to 80 consumers. (Meyners et al, 2014;Vidal et al, 2015;Avery & Joseph, 2019;Jaeger et al, 2019). Some recent studies have used the CATA method to characterize products such as hot and cold foods and beverages (Pramudya & Seo, 2018), solid products requiring oral processing prior to swallowing (Vidal et al, 2019) and vegetable and berry beverages, where the authors demonstrated the association between consumer's emotions and taste (Waehrens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%